دور الصناديق الوقفية في دعم التنمية المستدامة في ماليزيا - ميلودي, عمار; كرثيو, جمال; سلاطنية, ابتسام (جامعة الوادي - University of Eloued, 2021)
يعد وقف النقود إحدى الصيغ المبتكرة للعمل الوقفي حيث أجازه الفقهاء لما له من خصائص ومميزات تتماشى ومتطلبات العصر الحالي، وتعد الصناديق الوقفية صورة من صور وقف النقود، التي يمكن أن تكون السبيل لإحياء دور الوقف في التنمية المستدامة، وذلك من خلال قدرتها على تعبئة أموال الوقف عن طريق توسيع قاعدة الواقفين، بالإضافة إلى قدرتها على صيانة وتنمية أموال الوقف من خلال حسن إدارة الوقف وإستثمار أمواله، كذلك من خلال تمويلها للمشاريع التنموية في مجالات الصحة، التعليم، التكنولوجيا، الثقافة وحماية البيئة، كما أن للصناديق الوقفية دور مهم في مكافحة البطالة والفقر من خلال تمويل المؤسسات الصغيرة والمتوسطة والمشاريع المصغرة. يتضح أن الصناديق الوقفية ساهمت في تحقيق الأهداف المرجوة منها في دعم التنمية المستدامة في ماليزيا، وبالتالي يمكن تعميم تجربة الصناديق الوقفية في باقي الدول الإسلامية. The waqf of money is one of the innovative formulas for waqf work, where jurists authorized its properties and characteristics in line with the requirements of the present age, waqf funds are a form of stop money that can be a way of reviving the role of the waqf in sustainable development through its ability to ,obilizewaqf funds in the development of the waqf fund, and its ability to maintain and develop the waqf funds and invest its funds, as well as through funding for developmental projects in the fields of health, education, technology, culture and environmental protection, smal and medium-sized enterprises and micro entreprises. It is clean that waqf have contributed to acheieving their desired objectives in support of sustainable development in Malaysia experience of waqf funds can be generalized in others islamic countries. Key words: waqf, sustainable development, waqf funds, Malaysia.
The role of endowment funds in supporting sustainable development in Malaysia
مقال
Keywords: الوقف، الصناديق الوقفية، التنمية المستدامة، ماليزيا.